Teaching-learning of the "family" content in the General Practitioner’s training from education at work - Mabel Rocha Vázquez; Josè Aurelio Dìaz Quiñones; Norma Mur Villar (Medisur)
Background: the "family" content is of vital importance in the General Physician’s training in Cuba because the family is constituted as a group that is the objective of medical care. Objective: to develop a didactic strategy to improve the teaching-learning of the "family" content. Methods: development research with a materialistic dialectical approach, carried out at the Cienfuegos University of Medical Sciences, between July 2021 and March 2022, working from the visit to the family as an education at work modality. Methods were applied at the empirical, theoretical and mathematical sta-tistical levels that as a whole allowed achieving the expected objective. The proposal was organized in the diagnostic, design and evaluation stages. Results: potentialities and limitations were identified in the teaching-learning process of the "family" con-tent that allowed designing the strategy where the objectives constitute the guiding category, based on which the system of knowledge, skills and values is organized, structured from the stages of the visit to the family, seen in a systemic way, for which aspects of the method, the form, the means and the evaluation system are dealt with, in close relation with the academic, the attentional labor and the research aspects. Conclusions: the designed strategy is derived from the results obtained in the diagnosis and was valued by specialists as useful, inclusive, systemic and applicable, all of which supports its relevance.